Nghiên cứu xây dựng nguyên lý thay thế thuốc phóng cho các loại đạn pháo hiện có - Chương, Nguyễn Như; Điện, Trần Đăng (Journal of Computer Science and Cybernetics, 2016)
The purpose of this paper is to present one principle of the equivalence in the replacing the kinds be applicable to fundamental repairs and a new design of bullets.